2011
DOI: 10.1177/875512251102700103
|View full text |Cite
|
Sign up to set email alerts
|

Training Community Pharmacy Technicians about Their Roles in the Provision of Medication Therapy Management Services

Abstract: Researchers have identified barriers to providing medication therapy management (MTM) services in the community pharmacy setting. 1 Barriers perceived by pharmacists include the lack of pharmacists' training in the elements of MTM, resources to support the service, and personnel to assist pharmacists in the provision of the service. 1,2Incorporating pharmacy technicians in the process may help to decrease perceived barriers. 2 Not all elements required for the completion of MTM cases require the clinical judgm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 9 publications
3
9
0
Order By: Relevance
“…That said, only 59.7% of pharmacy technicians believed that they had the necessary knowledge and skills to assist with MTM compared with 91.9% of pharmacists (P < 0.01). Our findings align with those of Pattin et al, 20 who concluded that pharmacy technicians are willing to assist with MTM services; however, appropriate training is necessary for it to be effective. This finding further supports implementation strategies focusing on training pharmacy technicians on MTM services, as they already believe that they have the necessary time and support.…”
Section: Discussionsupporting
confidence: 91%
“…That said, only 59.7% of pharmacy technicians believed that they had the necessary knowledge and skills to assist with MTM compared with 91.9% of pharmacists (P < 0.01). Our findings align with those of Pattin et al, 20 who concluded that pharmacy technicians are willing to assist with MTM services; however, appropriate training is necessary for it to be effective. This finding further supports implementation strategies focusing on training pharmacy technicians on MTM services, as they already believe that they have the necessary time and support.…”
Section: Discussionsupporting
confidence: 91%
“…For example, the need to redefine workflow to incorporate MTM has been noted as a barrier . Defining and developing new roles for support staff have been emphasized . Moreover, community pharmacists have struggled with patient and prescriber understanding and acceptance of MTM services .…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Defining and developing new roles for support staff have been emphasized. 9,[11][12][13] Moreover, community pharmacists have struggled with patient and prescriber understanding and acceptance of MTM services. 8,[14][15][16] Additional barriers reported include high demand for dispensing-related activities, cumbersome MTM documentation, insufficient staff training, and inadequate staffing hours.…”
mentioning
confidence: 99%
“…Involvement of pharmacy technicians in areas other than dispensing medications have been continuously recognized. 1 Current literature has indicated that pharmacy technicians can contribute greatly in addressing drug shortage, 2 promoting pharmacy-based immunization, 3 assisting Medication Therapy Management, 4 and so on. In recent years, there has been an increase in pharmacists' provision of self-management education programs to patients in community pharmacy settings.…”
Section: Introductionmentioning
confidence: 99%